Revealing the deformation twinning nucleation mechanism of BCC HEAs. (11th February 2019) - Aitken, Zachary H.; Zhang, Yong-Wei
Abstract: Abstract : Deformation twinning has been frequently observed in body-centered cubic (BCC) high entropy alloys (HEAs), however, the underlying mechanism remains elusive. We perform molecular dynamics simulations on a representative BCC HEA nanopillar under high-symmetry compression, describe atomic details of deformation twinning, and propose a mechanism of twin nucleation from the surface. We find that twinned regions are formed by partial dislocations and that chemical heterogeneity can reduce local fault energy and promote stacking faults and twins. These results help to understand the propensity for stacking fault formation and twinning in HEAs and may guide the design of novel HEAs through control of active twinning mechanisms.